IMPLEMENTASI PERATURAN MENTERI PERTANIAN REPUBLIK INDONESIA NOMOR : 06/Permentan/ OT. 140/2/2015 TENTANG PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) DI KOTA PRABUMULIH - Farid Wadjdi (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
Based on the results of the study showed that the PUAP program in the City of Prabumulih, in general has been implemented according to procedures established by the Ministry of Agriculture, The influence of external environmental factors (environmental factors) namely cultural, social and political factors at one target group location, which causes delays in the distribution / realization of PUAP BLM funds, found factors that strengthen the implementation of the program include: Communication about the substance of the program delivered with both through socialization activities, Availability of field implementor human resources (advisors and PMT), Existence and self-help in Gapoktan sourced from principal savings, mandatory savings and voluntary savings, are strengthening community capital in Gapoktan institutions in addition to BLM PUAP stimulant funds, Team Resources resources authority Strong PUAP technique, High commitment and motivation from field implementation and found factors that weaken PUAP program implementation which include: Limitation of Gapoktan management human resources, Lack of budgetary resources, Limited resource authority for instructors, Lim sumberdaya limited information resources related to reporting mechanisms and the importance of reporting implementation even though our reporting technical has been consulted by PMT and the Provincial PUAP Guidance Team and declared no problem, Inadequate facility resources (supporting facilities) inhibited Fragmentation due to lack of coordination between the teams.